Malicious and benign maternal envy in Chinese childrearing. (September 2021) - Zong, Wenqing; Hawk, Skyler T.
Mothers utilize social comparisons to other parents to calibrate evaluations of themselves and their children, and these comparisons might prompt feelings of envy. Envy can either be malicious and destructive, or relatively more benign and constructive. This research examined distinctions between malicious and benign envy among Chinese mothers, differences from related emotions (i.e., resentment and admiration), and themes present in these experiences. An online sample of 152 Mainland Chinese mothers ( Mage = 46.91, SD = 2.26) recalled malicious and benign envy, admiration, and resentment experiences toward other parents and reported associated appraisals, motivations, and action tendencies. Results showed distinctions between malicious and benign maternal envy. Malicious envy included lower perceived control, higher perceived unfairness, and more desire to degrade the other than benign envy. Benevolent feelings toward the envied target characterized benign envy. Both forms of envy were linked to self-improvement motivation. Personal characteristics and achievements of both other parents and other children were prominent themes in mothers' experiences of various emotions. This research provides insights into how and why Chinese mothers experience different forms of envy, and has implications for research on social comparisons made in parenting contexts.